2018
DOI: 10.1016/j.comppsych.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the trends and correlates of major depressive episodes among juvenile offenders in the United States

Abstract: The prevalence of past year major depressive episodes is increasing for female juvenile offenders, highlighting a need for improved efforts to target these populations for prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
0
5
0
2
Order By: Relevance
“…In a recent study with older prisoners, depressive disorder and symptoms of depression were the most prevalent psychological issues reported (Stoliker & Galli, 2019). Similar to research with younger adults (Holzer et al, 2018), these results differed with respect to gender. Female prisoners were significantly more likely to report a depressive disorder as well as to receive mental health treatment prior to prison (Stoliker & Galli, 2019).…”
Section: Mental Healthmentioning
confidence: 49%
See 1 more Smart Citation
“…In a recent study with older prisoners, depressive disorder and symptoms of depression were the most prevalent psychological issues reported (Stoliker & Galli, 2019). Similar to research with younger adults (Holzer et al, 2018), these results differed with respect to gender. Female prisoners were significantly more likely to report a depressive disorder as well as to receive mental health treatment prior to prison (Stoliker & Galli, 2019).…”
Section: Mental Healthmentioning
confidence: 49%
“…Major depression has only been measured in NSDUH between 2005 and 2017. The criteria used to determine MDE are described in greater detail elsewhere (see Holzer et al, 2018). Demographic factors.…”
Section: Diagnostic and Statistical Manual Of Mental Disorders [Dsm]-based Items)mentioning
confidence: 99%
“…Several items were measured related to behavioral health. Consistent with recent NSDUH-based research ( Holzer et al, 2018 ; Oh et al, 2018 ), we used a dichotomous measure of one or more major depressive episodes (MDE) in the past 12 months (0 = no episode , 1 = one or more episodes ) ( American Psychiatric Association, 2013 ). We also examined self-reported cigarette use , binge alcohol use , cannabis use , and other illicit drug use (0 = no , 1 = yes ).…”
Section: Methodsmentioning
confidence: 99%
“…According to General Strain Theory (Agnew et al, 2002), delinquent behaviors are methods used by the offenders to offload negative emotions generated from daily strains. For example, excessive alcohol consumption and illicit drug use are employed by young people to soothe their negative emotions and uplift their moods (Holzer et al, 2018). Matsuura et al (2013) found that a high level of depression was associated with a high level of aggressive behavior among Japanese female juvenile offenders.…”
Section: Psychological Risk Factors In Juvenile Mental Health and Del...mentioning
confidence: 99%